The Ramsey number r(K1,3, C4, K4) - Klamroth, Kathrin; Mengersen, Ingrid (Utilitas Mathematica, 1997)
We will prove that r(K1,3, C4, K4) = 16. This fills one of the gaps in the tables of three color Ramsey numbers for graphs of order at most four presented in [1]. Moreover we consider three color Ramsey numbers concerning the graph 2K2.